2021
DOI: 10.1186/s13023-021-01973-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of serum interleukin-10 are associated with poor outcome in adult hemophagocytic lymphohistiocytosis patients

Abstract: Background Interleukin-10 (IL-10) is an independent factor for predicting adverse outcomes in pediatric patients with hemophagocytic lymphohistiocytosis (HLH). However, little is known about its prognostic value in adult patients. Methods This single center retrospective study was conducted to explore the prognostic value of IL-10 in 101 adults newly diagnosed with HLH. The serum interleukin levels were quantitatively determined by chemiluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
3
6
0
Order By: Relevance
“…EBV was the main trigger in infectious-related HLH and tended to imply poor survival in our cohort. Nearly all the malignancy-related HLH patients had lymphomas, consistent with other adult HLH studies [3,5,11,14]. It was noteworthy that infections were one of the major complications in patients with malignancies because of immune deficiency.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…EBV was the main trigger in infectious-related HLH and tended to imply poor survival in our cohort. Nearly all the malignancy-related HLH patients had lymphomas, consistent with other adult HLH studies [3,5,11,14]. It was noteworthy that infections were one of the major complications in patients with malignancies because of immune deficiency.…”
Section: Discussionsupporting
confidence: 85%
“…Yang et al [13] discovered that IL-6, IL-10, and IFN-γ were moderately or significantly elevated in most adult HLH patients and associated with several clinical features. Furthermore, elevated IL-10 was an independent risk factor for worse outcomes in children and adults with HLH [14,15]. We found that IL-10, IL-6, and IFN-γ were elevated in 93.3%, 91.1%, and 63.3% of patients.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The poor prognosis of HLH has been linked to laboratory abnormalities such as low platelet counts, low albumin levels, high bilirubin levels, and high ferritin levels, among others, according to previous research [13,41]. In our cohort, thrombocytopenia was revealed to be an independent predictor for both 30-day mortality and overall mortality.…”
Section: Discussionsupporting
confidence: 59%